Biomonitoring of urban ultrafine particle exposure and associated health effects - Elizabeth Miriam Fireman; Einat Fireman Klein; Mor Dabach; Emilia Hardak (International Journal of Public Health, 2026)
Objective To assess the health impact of industrial and urban air pollution in the Haifa Bay area using biological monitoring of micro- and ultrafine particles (UFPs), and to examine their associations with functional, inflammatory, and clinical outcomes. Methods The study included 99 hospital staff members: 50 from Bnai Zion Medical Center in the Haifa Bay area and 49 from Tel Aviv Medical Center as controls. Participants underwent spirometry, fractional exhaled nitric oxide (FeNO) measurement, exhaled breath condensate (EBC) and saliva collection, and completed a health questionnaire. Assessments were repeated after 1 year. Latent class analysis (LCA) was used to identify homogeneous subgroups based on biological and clinical parameters. Results LCA identified a cluster characterized by higher body mass index, increased UFP concentrations in EBC, and elevated salivary LDH-calcium levels. This cluster consisted predominantly of participants from Haifa and showed higher salivary lymphocyte counts. Participants in this subgroup also reported more frequent respiratory symptoms, including cough, sputum production, and atopic complaints. Conclusion Biological monitoring of nanosized particles may provide early indicators of adverse health effects associated with urban-industrial air pollution exposure.